Analisis Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan pada Counter Handhphone â€œVenus Cellularâ€ Tangerang - Dewi, Risfa; Suseno, Andri; Adhi, Mertha Widiyastuti (Syntax Idea, 2021)
The purpose of this study was to analyze the Effect of Product Quality on Customer Satisfaction on Handhphone Counter "Venus Cellular" Tangerang. This type of research used in writing is descriptive research, using qualitative approach. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. The phenomenon can be the form, activity, characteristics, changes, relationships, similarities, and differences between phenomena with each other. The implications of this make a quality brand will create an image of the product itself in the mind of the customer and make the basic motivation for customers in choosing a product. A product is said to have good quality if it has a positive impact on the company which includes increasing sales and improving the company's image in the eyes of the public, as well as increasing public knowledge of the use of the product, thus the quality of a product will have an effect in customer purchasing decisions. This is also done by venus cellular tangerang customers in making product purchase decisions by paying attention and considering the brand image and product quality owned by venus cellular Tangerang. The implications of this make a quality brand will create an image of the product itself in the mind of the customer and make the basic motivation for customers in choosing a product. A product is said to have good quality if it has a positive impact on the company which includes increasing sales and improving the company's image in the eyes of the public, as well as increasing public knowledge of the use of the product, thus the quality of a product will have an effect in customer purchasing decisions.